Synthesis, Characterization and Thermal Study of Phenanthroline Adducts of Zn(II) and Cd(II) Complexes of bis-N-Alkyl-N-phenyl dithiocarbamates - C. Onwudiwe, Damian; A. Ajibade*, Peter (Asian Journal of Chemistry, 2013)
Phenanthroline adducts of Zn(II) and Cd(II) complexes of N-alkyl-N-phenyl dithiocarbamate has been synthesized and characterized. The compounds formulated as [Zn(Rpdtc)2phen] and [Cd(Rpdtc)2phen], (where R = methyl, ethyl, butyl; p = phenyl; phen = 1,10-phenanthroline) were characterized by elemental analysis, FTIR, 1H NMR and 13C NMR spectroscopy. The octahedral geometry around the metal ions consists of two molecules of chelating dithiocarbamate and one molecule of phenanthroline ligands. Thermogravimetric studies show that the Zn(II) adducts undergo similar decomposition profile via the isothiocyanate to the ZnS whereas the Cd(II) adducts undergo a complex and different decomposition pattern.